Aspectos psicoafectivos de madres adoptantes y su intervención en el proceso de adopción y crianza (2021)
The main objective of this research is to identify the psycho-affective aspects experienced by mothers in the adoption and upbringing process in three (3) cases in the municipality of Roldanillo, taking into account the provisions and procedures required for adoption in Colombia. The theories addressed integrate the situations faced by the adopted child in adapting to the family group, the affective bonding and the fears and questions about upbringing. The methodology used is qualitative, making use of a semi-structured interview that allowed the collection of the mothers' narratives regarding their fears and insecurities, finding fears such as possible rejection for not being parents and possible reactions of rebellion and abandonment on the part of the adopted child when he/she reaches adolescence or adulthood.